Wacana Tujaqi pada prosesi adat perkawinan masyarakat Suwawa Provinsi Gorontalo - Umar, Fatmah AR. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The purpose of this research is to explain the scheme, actors, setting, and themes of tujaqi discourse in the procession of marriage culture in Suwawa society, Gorontalo Province, at the stages of motolobalango, momanato, and moponika. This research uses a qualitative approach. The results of this research show that (1) the scheme of tujaqi discourse in the marriage procession of Suwawa society, Gorontalo Province, follows a straightforward structure (beginning, middle, and end); (2) the actors involved in tujaqi discourse consist of various components, ranging from senior officials to the general public, including children; (3) the setting of tujaqi discourse includes patterned settings and spontaneous settings; and (4) the general themes of tujaqi discourse in the marriage procession of Suwawa society, Gorontalo Province, are struggle, sacrifice, and confession.